Aloe Vera for Protects Skin Tissues from The Damaging Impacts of Ultraviolet Radiation (International Journal of Advanced Medical Sciences and Technology (IJAMST), 2023)
When Overexposure to sun UV radiation leads to skin damage and increases the risk of skin cancer; thus, it is a factor in aging, which accelerate skin aging and increases the risk of skin cancer. To determine the Photoprotective potential was evaluated by biomechanical measurements of tissue and histopathological examination of the skin. Showed The skin group irradiated with exposed for 4 h to UV (UV lamps, wavelength 365 nm, power 6 W) without Aloe vera showed significant biomechanical measurements of tissues and histopathological change and showed skin necrosis of dermal collagen. The Treatment with Aloe vera protected skin tissues against UV exposure for 4 h to UV light (UV lamps, wavelength 365 nm, power 6 W damage by biomechanical measurements of tissues restoring histopathological changes. The extracted Aloe vera is shown.